2019
DOI: 10.21873/cgp.20167
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Gremlin1 Promotes Proliferation and Epithelial Mesenchymal Transition in Gastric Cancer Cells and Correlates With Poor Prognosis of Patients With Gastric Cancer

Abstract: Background/Aim: Gremlin1 (GREM1) plays an important role in certain malignancies by antagonising bone morphogenetic proteins and regulating angiogenesis directly/indirectly. The present study aimed to investigate the role of Gremlin1 in the development and progression of gastric cancer (GC). Materials and Methods: Expression of GREM1 in GCs was examined using quantitative real time PCR and The Cancer Genomic Atlas (TCGA) data. Influence on cellular functions was determined in both Gremlin1 knockdown and overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Not only are VEGF inhibitors directly responsible for downregulation of angiogenesis but the literature has suggested other compounds not specific to VEGF inhibition can downregulate angiogenesis. Bae et al suggested that metformin can inhibit the indirect feedback loop between CXCL8 and PTPRD (protein tyrosine phosphatase receptor delta) [119]. PTPRD downregulation is seen in gastric cancer leading to poorer overall survivals, while this axis has been shown to promote angiogenesis [119].…”
Section: Cancer-associated Fibroblasts and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are VEGF inhibitors directly responsible for downregulation of angiogenesis but the literature has suggested other compounds not specific to VEGF inhibition can downregulate angiogenesis. Bae et al suggested that metformin can inhibit the indirect feedback loop between CXCL8 and PTPRD (protein tyrosine phosphatase receptor delta) [119]. PTPRD downregulation is seen in gastric cancer leading to poorer overall survivals, while this axis has been shown to promote angiogenesis [119].…”
Section: Cancer-associated Fibroblasts and Angiogenesismentioning
confidence: 99%
“…Bae et al suggested that metformin can inhibit the indirect feedback loop between CXCL8 and PTPRD (protein tyrosine phosphatase receptor delta) [119]. PTPRD downregulation is seen in gastric cancer leading to poorer overall survivals, while this axis has been shown to promote angiogenesis [119]. A new compound, 5,6,7-trimethoxy flavonoid salicylate derivatives, was found to potently inhibit not only VEGF but also HIFa and may be effective in altering the angiogenic and hypoxic conditions of the tumor microenvironment [120].…”
Section: Cancer-associated Fibroblasts and Angiogenesismentioning
confidence: 99%
“…Then, we used TGF-β1 at the optimal concentration of 5 ng/ml (Figure S2A-D) to stimulate HPF-a cells and veri ed that GREM1 expression rst increased and then decreased in a time-dependent manner, reaching a peak at 1 h (Figure 3H and I). Many studies have examined the function of Grem1 in brosis [16,17,18,19], but its mechanism is still unclear, and we will mainly discuss the mechanism by which Grem1 causes pulmonary brosis. We generated a bubble chart of the signaling pathways related to the occurrence and development of brosis (Figure 3J) and performed protein network interaction analysis (PPI) on the genes in these signaling pathways to identify speci c targets of brosis (Figure 3K).…”
Section: Analysis Of Broblast Subtypesmentioning
confidence: 99%
“…Physiologically, EMT can be observed during embryogenesis, tissue development and wound healing [48]. It is also a common phenomenon during carcinogenesis and can either induce or coexist with various malignancies such as breast cancer, thyroid cancer, cholangiocarcinoma, non-small cell lung carcinoma, colorectal cancer, inflammatory bowel disease or GC [49][50][51][52][53][54][55][56][57][58][59][60]. During the EMT process, ECs undergo a series of biochemical reactions that eventually lead to alterations in the cells' morphology, especially the loss of the polarity of cells [17,61].…”
Section: Figurementioning
confidence: 99%
“…Neutrophils can induce EMT in tumor cells, thereby increasing the migratory ability and invasiveness of GC cells [87]. Not only the elevated absolute peripheral blood neutrophil counts but also the neutrophil/lymphocyte ratio, and neutrophil infiltration in the tumor microenvironment, all make up for poor prognosis [55]. The neutrophil/lymphocyte ratio is a significant prognostic factor in GC progression.…”
Section: Tumor-associated Neutrophilsmentioning
confidence: 99%